Mini Review: Ekstrak Sirsak (Annona muricata Linn.) untuk Terapi Kanker - Widyastuti, Dyah Ayu; Nurdyansyah, Fafa (Jurnal Ilmu Pangan dan Hasil Pertanian, 2018)
Cancer is one of the killer diseases in the world. The number of cancer patients is grow rapidly as world populations grow. That fact trigger medical world to develop a more effective with lower side effect therapy for cancer. One of the therapy which developed is natural therapy with plant extracts, such as soursop (A. muricata Linn.) extract. Soursop has chemical matter called acetogenin which able to induce apoptosis by inhibit ATP production in cellular respiration. Acetogenin also inhibit Bcl-2 protein activity so cancer cell proliferation is also inhibited. Those leads to inhibition of uncontrolled cell proliferation in cancer patients. Soursop (A. muricata Linn.) extract for cancer therapy has to be developed to determine the optimal doses, longterm safety, and possible side effect that may inflicted so this therapy would be safe for cancer patients.